Species composition and associated gastropods of the seagrass beds in Kataisan, San Jose, Tacloban City - Peñaranda, Janille S. (2022)
Seagrass meadows are dynamic ecosystems of the intertidal zones. The ecosystem provides a wide range of services but are often overlooked by many. Several marine organisms inhabit and depend their trophic habits on the meadows such as the gastropods. Gastropods-seagrass associations are common because of the grazing activity of the molluscan group: they may feed on epiphytes attached to the leaf blades of the seagrass, or feed directly on the leaf blades. A study on determining the species composition of seagrass and its associated gastropods was conducted in Kataisan, San Jose, Tacloban City. The estimated percent cover of seagrass beds in Kataisan was 51.23%. The beds were composed of Cymodocea serrulata and Halodule uninervis. Mean percent composition of C. Serrulata was 98.18% while H. Uninervis was 5%. There were three species of gastropod identified in the study site. The most abundant species was Canarium urceus (=Strombus urceus) having a total of 171 individuals collected. Species diversity (H'= 0.170; D= 0.066) and richness (DMg= 0.386; DMn= 0.010) values suggests that the gastropod community in Kataisan is in poor condition. Natural and man-made threats such as typhoons and unregulated gleaning, are linked to the decline of seagrass cover and gastropod population in Kataisan.